The Effectiveness of Mandatory Curriculum Courses in Promoting Students' Civic Engagement in Higher Education - Agung Tesa Gumilar; Rahmat Rahmat; Cecep Darmawan; Leni Anggraeni (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2025)
This study aims to examine the effectiveness of the Mandatory Curriculum Courses (Mata Kuliah Wajib Kurikulum or MKWK) in fostering civic engagement among university students. While previous research has emphasized the role of civic education in shaping character and social awareness, limited studies have specifically explored the contribution of MKWK as part of a national curriculum policy to enhancing civic engagement, particularly in technical and vocational higher education institutions. This study addresses this research gap by focusing on the implementation of MKWK in three different universities: ITB, POLBAN, and Telkom University. A quantitative approach was employed, using a closed-ended Likert-scale questionnaire distributed to active students from each institution. The collected data were analyzed using Pearson correlation to determine the relationship between MKWK and civic engagement, as well as simple linear regression to assess the level of contribution. The results indicate that students' perceptions of MKWK fall into the very high category, with the majority assigning scores in categories 5 and 4. These findings are supported by statistical analysis, showing a significant relationship between MKWK implementation and increased civic engagement, as indicated by a tvalue of 15.883—far exceeding the critical ttable value of 1.652. Regression analysis reveals that MKWK contributes 56.3% to students' political participation, collective action, and community service. These results suggest that experiential and socially interactive learning approaches within MKWK play a crucial role in strengthening civic engagement in higher education settings.Keywords: civic engagement, MKWK, higher education, student participation